Regulating own and teammates` emotions prior to competition - Friesen, A.; Stanley, D.; Devonport, T.; Lane, A. M. (Movement & Sport Sciences - Science & Motricité, 2019)
We examined intra- and interpersonal emotion regulation in the hour prior to athletic competition. Specifically, we investigated the extent to which differences between experienced and desired emotions were related to emotion regulation processes. Participants (n?=?114) from team/doubles sport rated their experienced and desired emotions before a recent competition, and listed strategies used to regulate emotions reporting frequency, effectiveness, and self-efficacy for each strategy used. They followed the same procedure in relation to perceived emotions in a teammate. Results show athletes who experienced emotions close to their desired states reported significantly higher regulatory emotional self-efficacy than those further from their desired states. Further, their emotion regulation strategies were used more frequently and were more effective. Qualitative results indicated that participants attempted to regulate similar emotions in themselves and others, but used different strategies to accomplish these tasks to different degrees of frequency. The findings highlight the role of self-efficacy in emotion regulation; an individual difference variable which merits attention in future emotion regulation interventions.